(untitled) (Journal of the College of Basic Education, 2025)
The genus Acinetobacter currently contains 34 species, the vast majority of which are not regularly implicated in causing infection. However, incidences of hospital-acquired infection with Acinetobacter species are increasing, mainly due to the rise in the number of infections caused by the species Acinetobacter baumannii in immunocompromised patients, particularly in intensive care units (ICUs). One hundred fifty clinical isolates were collected from burn units and wounds of both genders attending a burn hospital in Medical City in Baghdad, Iraq. All collected isolates were cultured on Mac-Conkey agar, blood agar, and CHROMagar orientation medium for the diagnosis of Acinetobacter baumannii isolates based on morphological and biochemical characteristics. The Vitek system was also used to identify the isolates at the species level. Silver nanoparticles (AgNPs) prepared from the hot extracts of Eucalyptus, and the crystallinity of synthesized AgNPs was investigated by an X-ray diffraction (XRD) technique and corresponding XRD patterns. In this study, we evaluated the antimicrobial and anti-biofilm activity of AgNPs against X-ray diffraction (XRD) A. baumannii. The results of the anti-biofilm activity showed AgNPs exhibited inhibition or reduction in biofilm formation at concentrations of 150, 75, and 37.5 µg/ml. Also the results of antimicrobial activity in Minimal Inhibitory Concentration (MIC) exhibited by the Eucalyptus Critriodora/ Silver (EK AG) against tested A. baumannii showed the concentration 31.5.µg/ml was inhibiting the growth of A.baumannii isolates in percent of 50% (4/8), while concentrations 18.7µg/ml were inhibitory for isolates, whilst antimicrobial activity in MIC exhibited by the EK plant against tested A.baumannii the concentration 150.µg/ml was inhibiting the growth of A.baumannii isolates in percent of 50% (4/8), while concentrations 75 µg/ml were inhibitory for isolates. In conclusion, the silver nanoparticles (AgNPs) have antimicrobial and antibiofilm activities against the (XDR) A. baumannii isolates under study.